Application of Jean Meeus Astronomical Algorithms in Formulating a Unified Global Hijri Calendar - Perkasa, Eza Budi; Irawadi, Syafrul; Sugihartono, Tri (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2025)
Indonesia should have a trusted institution to determine the beginning of the Hijri month. To date, the determination of the beginning of the Hijri month has not been standardized because each Islamic community organization has its own criteria. One of the criteria that will be discussed in this study is the 2016 Istanbul criteria which gave birth to the concept of a Unified Global Hijri Calendar. However, fulfilling these criteria method is still not agreed upon by experts, making it difficult to socialize to the public. This calendar has been used since 1447 AH/2025 AD. This study aims to provide a deeper understanding of these criteria and also attempts to implement Jean Meeus' astronomical algorithms to obtain the necessary ephemeris data. During the research process, regional datasets will be prepared according to their respective topographical conditions. The data used include the name of the region, the name of the country, latitude, longitude, and altitude. From the preparation, information will be obtained in the form of regions that can represent the time of the beginning of the Hijri month.